2018
DOI: 10.1016/j.anucene.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

On the use of CALPHAD-based enthalpy-temperature relations in suboxidized corium plane front solidification modelling

Abstract: The knowledge of in-vessel corium behaviour and associated risk of vessel failure are matters of prime interest within the framework of Severe Accident studies in a Light Water Reactor. Core meltdown during a severe accident results into formation of a corium pool at the bottom of the reactor vessel. This corium pool undergoes a density dependent liquid separation, thus exhibiting stratification into different phases. The distribution of phases depends on the time since the phase density depends on both temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Thus, as a first approach, we have chosen constant liquidus temperatures for the oxide and metallic layers. In [20], it is also shown that the radial variation of composition in the solid crust remains small (maximum of ≈ 9.5 % for the mass fraction of ZrO 2 ) in comparison to the variation of composition in the liquid. However, the crust model and its coupling with the pool were developed in such a way that more complex models could be easily plugged in, e.g.…”
Section: Crust Composition and Thermodynamic Closuresmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, as a first approach, we have chosen constant liquidus temperatures for the oxide and metallic layers. In [20], it is also shown that the radial variation of composition in the solid crust remains small (maximum of ≈ 9.5 % for the mass fraction of ZrO 2 ) in comparison to the variation of composition in the liquid. However, the crust model and its coupling with the pool were developed in such a way that more complex models could be easily plugged in, e.g.…”
Section: Crust Composition and Thermodynamic Closuresmentioning
confidence: 95%
“…At this stage, the crust composition treatment and thermodynamic closures remain simple while being qualitatively coherent (and probably quantitatively at the first order) to regain the expected physical behavior of the coupling at the interface between the pool and its crust. Indeed, it is shown in [20] that, for a given pool composition, the variation of the liquidus temperature of the oxide pool remains small (less than 50 K). Plus, we show in the following that for usual reactor case calculations, the metallic pool layers do not lose enough power in the crust in such a way that the interface temperature of its facing oxidic crust stays well above the solidification temperature.…”
Section: Crust Composition and Thermodynamic Closuresmentioning
confidence: 99%
See 1 more Smart Citation